2016
DOI: 10.1186/s12894-016-0179-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between depression and overactive bladder/urinary incontinence symptoms in the clinical OAB population

Abstract: BackgroundTo investigate the relationship between depression and overactive bladder (OAB)/urinary incontinence symptoms among the clinical OAB population.MethodsPatients who were diagnosed with overactive bladder (OAB) and age-matched control subjects without OAB were enrolled. Depression symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS-D). OAB/incontinence symptoms were assessed using the validated questionnaires: ICIQ-UI, ICIQ-OAB, UDI-6, IIQ-7, and OAB-q.Results27.5 % of OAB pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 24 publications
(31 reference statements)
5
60
1
3
Order By: Relevance
“…In the Korean study by Lim et al, the US studies by Lai et al, and a similar Brazilian study by Melotti et al, UI severity was positively correlated with anxiety, depression, and stress measures, even when different outcome measures were used. 57, 23, 25 The consistency of these results improve the credibility of our findings that worsening UI severity is an important factor associated with mental health. In women reporting UI in our study, UI severity scores ranged from 1.84–9.44.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the Korean study by Lim et al, the US studies by Lai et al, and a similar Brazilian study by Melotti et al, UI severity was positively correlated with anxiety, depression, and stress measures, even when different outcome measures were used. 57, 23, 25 The consistency of these results improve the credibility of our findings that worsening UI severity is an important factor associated with mental health. In women reporting UI in our study, UI severity scores ranged from 1.84–9.44.…”
Section: Discussionsupporting
confidence: 78%
“…Other groups have studied mental health factors in adults seeking treatment for overactive bladder (OAB). 57 Together, these studies showed that OAB was associated with higher anxiety, depression, and sleep disturbance compared to controls. Again, the comparison groups in these studies were control participants without LUTS.…”
Section: Discussionmentioning
confidence: 92%
“…Not only do these two symptoms coexist, they often respond to the same treatment and exacerbate each other [17]. In addition to pain, urinary dysfunction has also been reported to be correlated with severity of depression [50]. Interestingly, treatment for depression using duloxetine, a serotonin noradrenergic uptake inhibitor, has been shown to improve urinary symptoms [51].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that at baseline, those with PHQ‐8 scores ≥10 had significantly higher ICSI‐PI and OAB‐q ss scores suggesting a higher level of initial urinary bother. This is not surprising since OAB has been associated with affective symptoms, and OAB patients with depression report more severe urinary incontinence symptoms, greater bother and more impact on quality of life . Measuring the impact of neuromodulation on depressive symptoms was not the aim of this study, but depressive symptoms did decrease significantly over 6 months after neuromodulation in those with PHQ‐8 scores ≥10 at baseline.…”
Section: Discussionmentioning
confidence: 93%